Breaking teleprinter ciphers at Bletchley Park : general report on Tunny with emphasis on statistical methods (1945) /: general report on Tunny with emphasis on statistical methods (1945). ([2015]) - Good, Irving John; Michie, Donald; Timms, G (Geoffrey), 1903-1982
No abstract available